(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article proposes a reflection on the political aspects and technical and poetic procedures of the use of headphones in verbatim theater. First, the origins, development and procedures of verbatim theater are traced, with its roots in documentary theater and influences from radio documentaries. Then it is presented a particular kind of verbatim theater in which artists perform the sound mímesis in real time of testimonies heard through headphones on stage, in a double mediation of previously recorded voices. Next, different forms of staging and acting, and their consequences in headphone verbatim performances are presented. In the end, a reflection is proposed on the headphone verbatim as a form of meta-listening, regarding ethical aspects, the degrees of manipulation of the documentary records used, and in relation to the media.